Pharmacogenetics of tenofovir clearance among Southern Africans living with HIV. Issue 4 (6th June 2023) - Cindi, Zinhle; Kawuma, Aida N.; Maartens, Gary; Bradford, Yuki; Sokhela, Simiso; Chandiwana, Nomathemba; Venter, Willem D. Francois; Wasmann, Roeland E.; Denti, Paolo; Wiesner, Lubbe; Ritchie, Marylyn D.; Haas, David W.; et al.
Abstract : Background: Tenofovir is a component of preferred combination antiretroviral therapy (ART) regimens in Africa. Few pharmacogenetic studies have been conducted on tenofovir exposure in Africa, where genetic diversity is greatest. Objective: We characterized the pharmacogenetics of plasma tenofovir clearance in Southern Africans receiving tenofovir disoproxil fumarate (TDF) or tenofovir alafenamide (TAF). Methods: Adults randomized to TAF or TDF in dolutegravir-containing arms of the ADVANCE trial (NCT03122262) were studied. Linear regression models stratified by study arm examined associations with unexplained variability in tenofovir clearance. We investigated genetic associations with polymorphisms selected a priori followed by genome-wide associations. Results: A total of 268 participants (138 and 130 in the TAF and TDF arm, respectively) were evaluable for associations. Among polymorphisms previously associated with any drug-related phenotype, IFNL4 rs12979860 was associated with more rapid tenofovir clearance in both arms (TAF: P = 0.003; TDF: P = 0.003). Genome-wide, the lowest P values for tenofovir clearance in TAF and TDF arms were LINC01684 rs9305223 ( P = 3.0 × 10 −8 ) and intergenic rs142693425 ( P = 1.4 × 10 −8 ), respectively. Conclusion: Among Southern Africans randomized to TAF or TDF in ADVANCE, unexplained variability in tenofovir clearance was associated with a polymorphism in IFNL4, an immune-response gene. It is unclear how this gene would affect tenofovir disposition.